Determinants of Labor International Migration In Java - Sitoresmi, Luthfiah Nur; Suman, Agus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
International labor migration is an important aspect in population dynamics and economic development, particularly in Java, which is the region with the largest number of Indonesian Migrant Workers (PMI). This phenomenon is influenced by various economic factors that drive individuals to seek employment opportunities abroad. This study aims to analyze the determinants of international labor migration in Java during the period 2017-2023, with independent variables including poverty, Gross Regional Domestic Product (GRDP), Open Unemployment Rate (OUR), and Provincial Minimum Wage (UMP). The analytical method used is panel data regression with a Fixed Effect Model (FEM) approach. The results indicate that the variables of poverty and Open Unemployment Rate (OUR) have a negative and significant effect on international labor migration. Meanwhile, the variables of Gross Regional Domestic Product (GRDP) and Provincial Minimum Wage (UMP) do not have a significant effect on international labor migration.